Magna Mater and the poet unmanned (Ovid, Fasti 4.179-372) - Catharine Edwards (Eugesta, 2021)
Ovid’s treatment of the Magna Mater festival in Fasti Book 4 resonates significantly both with his earlier work and with his exile poetry. The episode offers more than one potential figure, it is argued, for the poet and his traumatic experience of punishment at the hands of the emperor. Some significant parallels might prompt readers to perceive an analogy between Ovid, whose experience of exile is repeatedly figured as a painful wound, and Attis, the castrated acolyte of the Magna Mater. More compelling ultimately is the parallel between Ovid and Claudia Quinta, whose reputation, wrongly impugned, is vindicated by the goddess.